Vibrational Spectral Studies of Pure and Doped TGSP Crystals - N. Kartheeswari; K. Viswanathan (Journal of Spectroscopy)
Triglycine sulfate crystals (TGS) are an important class of ferroelectric materials. TGS have attracted many researches because of thier room temperature ferroelectric nature. TGS found wide applications in electronic and optical fields. In present work, pure and ADP-, KDP- (0.2 mol) doped TGSP crystals are grown from solution growth method. Grown crystals are subjected to UV-Vis, IR, and Raman spectral studies. Crystal structure of grown crystals is obtained from powder XRD pattern. Ferroelectric nature of grown crystals is tested using homemade Sawyer-Tower circuit. Electrical conductivity measurements are carried out for pure and doped TGSP crystals.